Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. The Effect of a training program based on Felder-Silverman model on improving reflective practices of Muslim bin Yasar Middle School teachers in RiyadhMr. Ahmad Ali Al-Bariqi, Co-Prof. Ahmad Hasan Al-Bdour2. STEM Program in Kindergarten in Australia and the possibility of benefiting from it in the Kingdom of Saudi ArabiaMrs. Tahani Mohammed Mougram Alshehri3. Reality of employing Blockchain technology in educational process in Saudi universities from point of view of faculty membersMrs. Shorouk Abdullah Tael Al-Sawat4. Employing artificial intelligence applications and their importance in the educational process from the point of view of computer teachersDr. Ashwaq Dahman Qirqaji5. Evaluation of the psychometric properties of the Arabic version of the Depression, Anxiety, and Stress Scale- 21 items (DASS-21) – A descriptive study on a sample of adolescents in Jeddah- Saudi ArabiaMrs. Walaa Salem Al-Shetaiwi, Co-Prof. Nawal Abdullah Al-Dhobaiban6. The relationship of shyness to self-concept among upper elementary school students  in the Area Al-Qasr Education DirectorateMrs. Rozeen Khalaf Mawadeh , Prof. Mikail Ibrahim
Keywords: Journal of Educational and Psychological Sciences